2017
DOI: 10.1016/j.vaccine.2017.03.077
|View full text |Cite
|
Sign up to set email alerts
|

Clinician-parent discussions about influenza vaccination of children and their association with vaccine acceptance

Abstract: Objective To examine how clinicians communicate with parents about influenza vaccination and the effect of these communication behaviors on parental vaccine decision-making. Study Design We performed a secondary analysis of data obtained from a cross-sectional observational study in which health supervision visits between pediatric clinicians and English-speaking parents of young children were videotaped. Eligible visits occurred during the 2011–2012 and 2013–2014 influenza seasons, included children ≥6 mont… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
43
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 66 publications
(45 citation statements)
references
References 21 publications
2
43
0
Order By: Relevance
“…Further exploration is warranted given data demonstrating the critical importance of provider vaccine communication in pediatric populations. [44][45][46] Varied health care use patterns also could contribute to undervaccination of preterm infants. Authors of a small study from Switzerland reported that some parents of preterm infants desired a "rest" after hospital discharge.…”
Section: Discussionmentioning
confidence: 99%
“…Further exploration is warranted given data demonstrating the critical importance of provider vaccine communication in pediatric populations. [44][45][46] Varied health care use patterns also could contribute to undervaccination of preterm infants. Authors of a small study from Switzerland reported that some parents of preterm infants desired a "rest" after hospital discharge.…”
Section: Discussionmentioning
confidence: 99%
“…For example, they could use evidencebased approaches, such as a presumptive vaccine recommendation or motivational interviewing, for parents who are identified as vaccine hesitant. [38][39][40][41] They also could address concerns raised in response to individual survey items. In this study, the association of some PACV items (eg, recommended number of vaccines) but not other items (eg, vaccine-preventable infection severity) with influenza vaccine declination suggests that certain topics may be more relevant to parental decisionmaking about influenza vaccination during the child' s hospitalization.…”
Section: Discussionmentioning
confidence: 99%
“…10 Studies have shown that parental acceptance of influenza vaccine was higher when clinicians discussed vaccination using a presumptive format (presume acceptance) rather than a participatory format (parents asked questions about vaccination rather than presume that they will accept the vaccine). 11,12 Teaching providers a presumptive format to initiate a vaccine discussion will be an important step to improve vaccination during future influenza seasons. It is interesting that admission of the child to the PICU or the presence of chronic medical conditions did not have a significant impact on parental decision to vaccinate their child.…”
Section: Discussionmentioning
confidence: 99%